High‐Resolution Vessel Wall MR Imaging in Diagnosis and Length Measurement of Cerebral Arterial Thrombosis: A Feasibility Study - Zhang, Chao; Dou, Weiqiang; Jiang, Shu; Dong, Dong; Wang, Xinyi (Journal of magnetic resonance imaging, 2022)
Background Detecting and measuring intraluminal thrombus has prognostic and therapeutic implications for stroke patients. Purpose To investigate the feasibility of 3D isotropic high‐resolution T1w‐CUBE imaging to detect and measure intraluminal thrombus in stroke patients. Study Type Retrospective. Subjects A total of 93 patients with acute (N = 39) and subacute (N = 54) stroke. Field Strength/Sequence A 3.0 T/spin‐echo echo‐planar diffusion‐weighted imaging (DWI), high‐resolution T1w‐CUBE imaging and 3D flow compensated gradient‐echo susceptibility‐weighted imaging (SWI). Assessment Data assessment was performed by three neuroradiologists with 11, 13, and 20 years of clinical experience. The accuracy of T1W‐CUBE and SWI in diagnosing thrombosis was compared by using digital subtraction angiography (DSA) as the reference. For thrombus length measurement, the image quality of proximal and distal thrombus of T1w‐CUBE images was first evaluated with a 4‐point rating system. Then, the proximal and distal positions to lesions were determined on T1w‐CUBE images and compared with those from DSA acquired during endovascular reperfusion therapy. If comparable both locations were found between CUBE and DSA, CUBE imaging can thus be considered for accurate measurement of thrombus length. Statistical Tests Fleiss' Kappa; the area under the receiver operating characteristic (ROC) curve (AUC); Pearson's chi‐squared test with Yates' continuity correction. Results Moderate‐to‐good interobserver agreements were validated with all Kappa coefficients higher than 0.40 in thrombus diagnosis and measurement. CUBE imaging showed higher clinical efficacy than SWI (AUC: 0.966 vs. 0.850) in thrombus diagnosis. Additionally, high quality of CUBE imaging was confirmed with 3 or 4 points rated by all three observers. Compared to intraoperative DSA, T1w CUBE showed consistent proximal and distal positions of thrombi in 16 of the 18 patients, validating the accuracy of T1w‐CUBE in measuring thrombus length. Data Conclusion T1w‐CUBE imaging has potential to facilitate diagnosis and measurement of intraluminal thrombus. Evidence Level 4 Technical Efficacy Stage 2